2010
DOI: 10.1097/htr.0b013e3181cd67ea
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Tracheostomized Patients With Severe Traumatic Brain Injury Following Implementation of a Specialized Multidisciplinary Tracheostomy Team

Abstract: Implementation of the tracheostomy team appears to have had positive clinical benefits for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 9 publications
0
40
0
1
Order By: Relevance
“…There is sufficient evidence that people are better managed with a tracheostomy team [94][95][96][97][98][99][100][101] including those with a traumatic brain injury [102]. Furthermore, there is support for those with saliva management issues to be managed better within a team setting [23,77,78,87,103].…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient evidence that people are better managed with a tracheostomy team [94][95][96][97][98][99][100][101] including those with a traumatic brain injury [102]. Furthermore, there is support for those with saliva management issues to be managed better within a team setting [23,77,78,87,103].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with Ward et al (2008) and similar to those from America reported over a decade ago (Manley et al 1999) suggesting that these issues are a challenge for clinicians internationally. The benefits of a hospital‐wide coordinated multidisciplinary team approach to tracheostomy management has been found to ensure team members feel supported, complications are reduced, goals are achieved more efficiently, the quality of care is improved, and time to decannulation and length of stay are decreased (Arora et al 2008, Dikeman and Kazandijian 2003, Garrubba et al 2009, Le Blanc et al 2009, Norwood et al 2004, Parker et al 2010, Tobin and Santamaria 2008). Consequently, it is critical that clinicians and their managers continue to address actively the issues that are preventing a team approach in their service.…”
Section: Discussionmentioning
confidence: 99%
“…Stay after ICU decreased over time, a higher proportion of decannulated patients were discharged, and the time to decannulation after ICU discharge decreased. In patients with traumatic brain injury, LeBlanc et al 32 found that a tracheostomy team resulted in a significantly shorter stay and greater use of speaking valves. de Mestral et al 33 reported their experience with the implementation of a tracheostomy team consisting of a surgeon, surgical resident, RT, speech-language pathologist, and clinical nurse specialist.…”
Section: Tracheostomy Teamsmentioning
confidence: 99%